Pridopidine Reverses Phencyclidine-Induced Memory Impairment - Sahlholm, Kristoffer; Valle-León, Marta; Fernández-Dueñas, Víctor; Ciruela, Francisco (Frontiers in Pharmacology, 2018)
Pridopidine is in clinical trials for Huntington’s disease treatment. Originally developed as a dopamine D2 receptor (D2R) ligand, pridopidine displays about 100-fold higher affinity for the sigma-1 receptor (sigma-1R). Interestingly, pridopidine slows disease progression and improves motor function in Huntington’s disease model mice and, in preliminarily reports, Huntington’s disease patients. The present study examined the anti-amnesic potential of pridopidine. Thus, memory impairment was produced in mice by administration of phencyclidine (PCP, 10 mg/kg/day) for 10 days, followed by 14 days’ treatment with pridopidine (6 mg/kg/day), or saline. Finally, novel object recognition performance was assessed in the animals. Mice receiving PCP and saline exhibited deficits in novel object recognition, as expected, while pridopidine treatment counteracted PCP-induced memory impairment. The effect of pridopidine was attenuated by co-administration of the sigma receptor antagonist, NE-100 (10 mg/kg). Our results suggest that pridopidine exerts anti-amnesic and potentially neuroprotective actions. These data provide new insights into the therapeutic potential of pridopidine as a pro-cognitive drug.